Physical Activity Intensity, Total Modes, and Neck Muscle Stiffness - Tanoto, Nicholas (Media Ilmu Keolahragaan Indonesia, 2021)
Background: Neck muscle stiffness is the most common finding of neck pain. The effect of physical activity on neck muscle stiffness is still showing various results. Currently, working from home as the result of COVID-19 pandemic had changed the daily physical activity of each person, including medical students. Objective: This study aims to determine the relationship between physical activity intensity along with total modes of activity and frequency of neck muscle stiffness events. Methods: This is an observational study with cross-sectional study design. Simple randomized sampling was used in this study. Data collection utilized modified EPIC-PAQ2. Data calculated and converted to MET-hour/week and units to assess physical activity intensity and total modes. Results: Physical activity intensity and total modes of activities showed no statistically significant relationship with the frequency of neck muscle stiffness in preclinical medical students in Faculty of Medicine, University of Sumatera Utara. Sex parameter showed significant relationship. Male category showed odd ratio of 0.358 (OR = 0.358, 95% CI) for developing more frequent neck muscle stiffness. Conclusion: More accurate studies have to be conducted to adjust confounding factors on the incidence of neck muscle stiffness.